If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x(6 + 4x) = 26 + x (6 * 6x + 4x * 6x) = 26 + x (36x + 24x2) = 26 + x Solving 36x + 24x2 = 26 + x Solving for variable 'x'. Reorder the terms: -26 + 36x + -1x + 24x2 = 26 + x + -26 + -1x Combine like terms: 36x + -1x = 35x -26 + 35x + 24x2 = 26 + x + -26 + -1x Reorder the terms: -26 + 35x + 24x2 = 26 + -26 + x + -1x Combine like terms: 26 + -26 = 0 -26 + 35x + 24x2 = 0 + x + -1x -26 + 35x + 24x2 = x + -1x Combine like terms: x + -1x = 0 -26 + 35x + 24x2 = 0 Factor a trinomial. (-2 + -1x)(13 + -24x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(13 + -24x)' equal to zero and attempt to solve: Simplifying 13 + -24x = 0 Solving 13 + -24x = 0 Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -24x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -24x = 0 + -13 -24x = 0 + -13 Combine like terms: 0 + -13 = -13 -24x = -13 Divide each side by '-24'. x = 0.5416666667 Simplifying x = 0.5416666667Solution
x = {-2, 0.5416666667}
| -8*v-2=-6(v-1) | | .125D-3(D-7)=5.125D-3 | | 21=-7*u+4(u+6) | | x^2-xy+3x^2+4xy= | | 2(v-7)+5*v=28 | | (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 | | 48-54+30= | | 63x^2-24x-15=0 |